PS-054 Operating Room Medicines Safety: identifying latex-free medicines packaging to create a user friendly database at a University Hospital. (24th February 2014) - Marques, M; Ribeiro Rama, AC; Loureiro, C
Abstract : Background: Natural rubber latex is related to at least 10% of anaphylaxis reactions under anaesthesia. Latex sensitisation increases, and can lead to allergic reactions, in some specific groups exposed to latex allergens, such as patients with multiple surgical procedures, spina bifida and congenital urogenital anomalies, and workers with occupational contact with latex. Multiple organ failure, beginning with bronchospasm and cardiovascular collapse are the usual intraoperative latex anaphylactic reactions. Literature provides some evidence that pharmaceutical vials can be a potential source of latex allergens, inducing allergic reactions. Purpose: To identify medicines packaging containing latex, stored at the Operating Room Department (OR). To create a database available for healthcare professional to consult. Materials and methods: Information was collected about the presence of latex in medicines packaging supplied since January 2012, by searching the Summary of Product Characteristics or directly contacting the pharmaceutical manufacturer. Medicines packaging includes: vials, ampoules, stoppers and syringes (plunger and barrel). Results: Medicines stored at OR included 166 generic names corresponding to 265 brand names. Of the 265 packages evaluated, 95.8% were latex free, information was absent in 3.8% and only 1 had latex in its package. We developed a database with ATC classification, generic name, brand name, manufacturer, latex or latex free package, accessible in paper form and electronically in a user friendly format. It will be regularly updated as we check the latex content of new products. Conclusions: We were able to provide information on the latex content of 96.2% of the medicines packaging. With the created database, we can efficiently provide a safe latex-free environment in the theatre for patient and healthcare professionals with known or suspected latex allergy. No conflict of interest.